PREVALENCE AND SOCIO-DEMOGRAPHIC RISK FACTORS OF GESTATIONAL DIABETIC MELLITUS AMONG WOMEN ATTENDING ANTENATAL CLINICS AT OBSTETRICS & GYNECOLOGY DEPARTMENT OF PEOPLES MEDICAL COLLEGE HOSPITAL NAWABSHAH, SINDH, PAKISTAN - Nusrat Nazir Siyal; Riaz Ahmed Mangi; Noor Ali Samoon; Jawaid Hussain Lighari; Naila Yousif; Parus Saleem (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Background: Gestational Diabetes Mellitus (GDM) is serious consequences for both maternal and neonatal health. The growing number of non-communicable diseases and related risk factors as well as the introduction of new World Health Organization diagnostic criteria for GDM are likely to impact the GDM prevalence in Pakistan.Aim: To determine the frequency and socio-demographic risk factors of GDM at obstetrics and Gynecology department of Peoples Medical College Hospital (PMCH), Nawabshah, Sindh, Pakistan.Methods: This cross-sectional study was conducted at the department of obstetrics & Gynecology PMCH, Nawabshah, Pakistan from May 2022 to July 2022. A total of 216 pregnant females of 2nd and 3rd trimester were included. Random blood sugar (RBS) evaluation was done by electronic glucometer. Women whose RBS was ≥140mg/dl, oral glucose tolerance test (OGTT) was done adopting standard protocols. After 1-hour, blood glucose value ≥180mg/dl was labeled as GDM. Association of various socio-domographic characteristics was assessed with GDM applying chi-square test taking p